Knowledge and its Objects: Revisiting the Bounds of Sense. (11th January 2017) - Cassam, Quassim
Abstract: The Kantian project of investigating the necessary structure of experience presupposes answers to three questions: what is the purpose of such an investigation, what is the source of necessary features of experience, and by what means is it possible to establish the necessary structure of experience? This paper is a critical examination of Strawson's answers to these questions in The Bounds of Sense and his later work. The realism that is implicit in The Bounds of Sense is much more explicit in Strawson's later work but relies on problematic assumptions about the relationship between epistemology and metaphysics.